2017
DOI: 10.1016/j.soilbio.2017.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Rhizosphere-associated bacterial network structure and spatial distribution differ significantly from bulk soil in wheat crop fields

Abstract: The spatial distribution of bacteria in bulk soil has been well studied, but little is known about the bacterial biogeography in the rhizosphere of crops. Here, we investigated bacterial distribution in bulk soil, loosely-and tightly-bound soils, from wheat fields distributed across 800,000 km 2 of the North China Plain. Bacterial community composition differed dramatically among bulk and rhizospheric soils, and bacterial diversity decreased with the root proximity. Soil pH correlated with bacterial community … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
139
3
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 242 publications
(185 citation statements)
references
References 76 publications
25
139
3
2
Order By: Relevance
“…This agreed with the result of the Mantel test, that soil pH had the biggest correlation of bacterial community composition ( r = 0.64, p < 0.001 in Appendix Table A2). Many studies have identified soil pH as the most important variable influencing bacterial community in both natural and agricultural ecosystems (Fan et al, ; Fierer & Jackson, ; Liu et al, ; Shen et al, ; Sun, Zhang, Guo, Wang, & Chu, ; Tripathi et al, ). The reason for this could be that bacterial species or strains are capable of optimal growth only within a narrow pH range (Lauber, Hamady, Knight, & Fierer, ; Ramirez, Craine, & Fierer, ), such that changes in environmental pH would directly deterministically select for species with different pH optima.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This agreed with the result of the Mantel test, that soil pH had the biggest correlation of bacterial community composition ( r = 0.64, p < 0.001 in Appendix Table A2). Many studies have identified soil pH as the most important variable influencing bacterial community in both natural and agricultural ecosystems (Fan et al, ; Fierer & Jackson, ; Liu et al, ; Shen et al, ; Sun, Zhang, Guo, Wang, & Chu, ; Tripathi et al, ). The reason for this could be that bacterial species or strains are capable of optimal growth only within a narrow pH range (Lauber, Hamady, Knight, & Fierer, ; Ramirez, Craine, & Fierer, ), such that changes in environmental pH would directly deterministically select for species with different pH optima.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, ecological communities that are geographically close to one another tend to have more similar species composition than geologically distant ones. Many studies have confirmed the existence of distance‐decay pattern in soil microbial communities (Chemidlin et al, ; Chu et al, ; Durrer et al, ; Fan et al, ; Martiny, Eisen, Penn, Allison, & Horner‐Devine, ; Shi et al, ; Terrat et al, ; Tuomisto, Ruokolainen, & Yli‐Halla, ; Wang, Lu, et al, ; Yang et al, ; Zhang et al, ). Such studies have also disentangled the contribution of habitat heterogeneity and biogeographic differences to distance‐decay patterns (Fan et al, ; Langenheder & Ragnarsson, ; Ramette & Tiedje, ; Ranjard et al, ; Shi et al, ; Zhang et al, ).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Bacteria and fungi, two major microbial communities, are vastly different in regard to their morphological traits, growth rates, environmental sensitivities and substrate utilizations . Numerous studies on soil ecosystems have demonstrated that both bacterial and fungal communities have responded to ecological mechanisms that drive compositional variations Fan et al, 2017). Until recently, dispersal limitation and environmental selection have been widely accepted as two of the principal forces driving microbial distribution (Martiny et al, 2006;Chu et al, 2016;Zhang et al, 2017;Zhang et al, 2018b), and the relative importance of these factors depends on spatial scales, habitat types and taxon traits (Hanson et al, 2012;Wu et al, 2013;Wang et al, 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…Interactions among different microbial species through mutualism, parasitism, competition or predation can cause complex co-occurrence networks (Faust and Raes, 2012). Network analysis has been increasingly used as a powerful analytical approach to explore the results of a set of interactions among microorganisms and biological complexity in microbial ecology in oceans (Aylward et al, 2015), soils (Fan et al, 2017;Xiao et al, 2018) and lakes (Kara et al, 2013). The topological network characteristics such as node number, edge number and clustering coefficient have been used to define the importance of species interactions in affecting community stability and ecosystem function (Cardona et al, 2016;Deng et al, 2016).…”
Section: Introductionmentioning
confidence: 99%